2020
DOI: 10.5530/ijpi.2020.2.41
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Pattern and Awareness of Migraine in Eastern Provinces, Saudi Arabia: A Descriptive Cross Sectional Study

Abstract: Objectives: This study aimed is to identify treatment pattern and awareness of migraine in Eastern provinces of Saudi Arabia. Methods: The survey questionnaire used to assess the awareness and treatment pattern of migraine was adopted from previous study. The questionnaire contains three sections. The first section contained of items related to demographic information of the participants. The second section contains to assess the knowledge of participants towards migraine. The third part of questionnaire conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This was a cross-sectional study conducted on 354 individuals using the International Headache Society (IHS) criteria [ 11 ]. Finally, in the eastern province, approximately 40% of study participants reported experiencing migraine headaches [ 12 ]. In a recent comprehensive study conducted across various regions of the kingdom, the prevalence of migraine was determined to be 27.4% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was a cross-sectional study conducted on 354 individuals using the International Headache Society (IHS) criteria [ 11 ]. Finally, in the eastern province, approximately 40% of study participants reported experiencing migraine headaches [ 12 ]. In a recent comprehensive study conducted across various regions of the kingdom, the prevalence of migraine was determined to be 27.4% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the final paper, nearly 40% of a study sample in Saudi Arabia's Eastern province were found to experience migraine headaches. However, the article directly asked if the participants had migraines without using any measuring tools [ 9 ]. A common disadvantage of these studies is that each one utilized a different methodology of evaluating migraine headaches, emphasizing the need for a large-scale study that presents migraine prevalence in various regions of Saudi Arabia using consistent criteria.…”
Section: Introductionmentioning
confidence: 99%
“…However, this astronomical percentage of migraineurs is inconsistent with the rest of the study reporting. In the final paper, nearly 40% of a study sample in Saudi Arabia's Eastern province were found to experience migraine headaches; However, the article directly asked if the participants had migraines without using any measuring tools [9]. A common disadvantage of these studies is that each one utilized a different methodology of evaluating migraine headaches, emphasizing the need for a large-scale study that presents migraine prevalence in various regions of Saudi Arabia using consistent criteria.…”
Section: Introductionmentioning
confidence: 99%